2017
DOI: 10.4067/s0718-95162017000400014
|View full text |Cite
|
Sign up to set email alerts
|

Natives helping foreigners?: The effect of inoculation of poplar with patagonian beneficial microorganisms

Abstract: Inoculation with microorganisms represents an opportunity to enhance tree production, directly affecting plant growth or survival at planting. The aim of the present study was to evaluate the effect of mixed inoculation with native mycorrhizae, two yeasts and one endophytic bacterium, on the growth of two poplar clones commonly used in Patagonia, Argentina. Yeasts and bacteria were selected base on their ability to produce IAA and siderophores, as well as P solubilization in-vitro. A greenhouse trial was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These results are in agreement with previous studies carried out in Patagonia, which reported that some native forest species, such as Araucaria araucana, Austrocedrus chilensis and different Nothofagus species, are capable of colonizing and growing rapidly on tephra deposits (González et al, 2014), which in several cases can be helped by microbial interactions at soil-root level (Marín et al, 2016;Mestre et al, 2017). For example, 17 months after the eruption of Hudson volcano, Vogel (1996) described the massive establishment of N. pumilio seedlings growing directly on the tephra.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with previous studies carried out in Patagonia, which reported that some native forest species, such as Araucaria araucana, Austrocedrus chilensis and different Nothofagus species, are capable of colonizing and growing rapidly on tephra deposits (González et al, 2014), which in several cases can be helped by microbial interactions at soil-root level (Marín et al, 2016;Mestre et al, 2017). For example, 17 months after the eruption of Hudson volcano, Vogel (1996) described the massive establishment of N. pumilio seedlings growing directly on the tephra.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that increased AM colonization, in this case, the addition of F. mosseae, can positively influence productive parameters, both under normal irrigation conditions and in situations of water shortage. The relationship between Patagonian yeasts and native mycorrhizal colonization has been reported in studies such as Mestre et al (2017), where a tendency of increased colonization of native mycorrhizae was observed in poplars inoculated with the native yeast Tausonia pullulans. Fracchia et al (2003) recorded an increase in mycorrhizal colonization in soybean (Glycine max) and red clover roots after double inoculation of F. mosseae and Rhodotorula mucilaginosa, when the yeast was inoculated before F. mosseae.…”
Section: Discussionmentioning
confidence: 74%
“…Currently it is well known that IAA production is widespread among soil bacteria that inhabit the rhizosphere of plants, and IAA production promotes growth and development (Egamberdieva et al, 2017;Viscardi et al, 2016); thus, this trait was our principal criterion for selection. Others have also noted that IAA production can be used for the selection of effective plant growth promoting rhizobacteria (Etesami et al, 2015;Mestre et al, 2017). The main IAA-producing bacteria belonging to the Aeromonas, Azotobacter, Bacillus, Burkholderia, Enterobacter, Pseudomonas, Rhizobium and Serratia genera have been isolated from different rhizospheric soils (Egamberdieva et al, 2017;Koo and Cho, 2009;Martinez-Viveros et al, 2010).…”
Section: Discussionmentioning
confidence: 99%